Splenic lymphangiomatosis in an adult patient Case report - Jiménez-Canizales, Carlos Eduardo (2022)
Lymphangiomas are benign malformations of the lymphatic system. They most often affect children and rarely adults. We present the case of a 36-year-old woman with a 6-month clinical picture of diffuse abdominal pain without peritoneal irritation associated with adynamia. As part of the studies, a computerized axial tomography with abdominal contrast was requested, which revealed multiple hypovascular hypodense splenic lesions with suspected diagnosis of lymphoproliferative lesions. For this reason, a diagnostic splenectomy was requested, which showed macroscopic, microscopic and immunohistochemical findings (positivity of cystic lesions for CD31 and D2-40) compatible with diffuse splenic lymphagiomatosis.